Ablation and molten layer flow simulation for plate model of SiO2f/SiO2 composite material using particle method - Gao, Junjie; Deng, Daiying; Luo, Xiaoguang; Han, Haitao; Yu, Jijun (Computers & fluids, 2024)
•Extension of MPS Method: This study extends the Moving Particle Semi-Implicit (MPS) method from simulating free flow to modeling ablation and surface morphology of SiO₂f/SiO₂ composite materials. It addresses challenges associated with aerodynamic heating, extremely viscous flows, and phase changes between solid-liquid and liquid-gas states.•Introduction of a Novel Simulation Method: A novel simulation approach is introduced for SiO₂f/SiO₂ composites that accounts for heat transfer, melting, solidification, evaporation behavior, and viscosity variations with temperature.•Innovative Application of Conceptual Particles: The method employs conceptual particles to establish models for applying heat flux and airflow shear force. This ensures that these forces are accurately applied solely to the upper surface of models composed of solid, wall, and dummy particles.•Advancement over Previous Algorithms: In contrast to previous algorithms for silicon-based materials, this method solves the complete Navier-Stokes and continuity equations based on the MPS method. This advancement enables the consideration of unsteady effects, two- and three-dimensional simulations, and additional influencing factors such as gravity and surface tension.•Validation and Examination of Effects: The ablative regression of a plate model was validated against experimental results for SiO₂f/SiO₂ composites, demonstrating that the particle method accurately simulates the ablation process. In this paper, the moving particle semi-implicit method (MPS) is extended from calculating free mobility to simulating the extremely viscous and temperature-dependent molten layer flow of SiO2f/SiO2 composite material under aerodynamic heating conditions, which includes strong heating and shear of incoming flow. A method for applying heat flux and airflow shear, based on the conceptual particle approach, has been established. Heat transfer, melting, solidification, and evaporation behaviors are considered, with temperature-dependent viscosity variations also accounted for. The ablative regression of the plate model is verified using experimental results of the SiO2f/SiO2 composite material, and results from convergence analysis demonstrate the accuracy of the space step size selection. Surface morphology analysis through three-dimensional computation indicates that the extended particle method also accurately describes the surface morphology of SiO2f/SiO2 composite material under aerodynamic heating conditions. Thus, the extended particle method accurately simulates both the ablation process and the surface morphology of the SiO2f/SiO2 composite material. The influences of acceleration and surface tension are discussed. Ablative recession, when subject to acceleration, is smaller than that observed in its absence. When exposed to surface tension, the liquid layer tends to form a spherical shape, and the particles behave as a cohesive unit, resulting in smaller ablative recession than in the absence of surface tension.